Transformational Philanthropy Model: A Strategy for Sustainable Community Development in Indonesia - Padli, Hardiansyah; Sahroni, Abdullah (MD Research Center Yogyakarta, 2026)
This study identifies three core pillars for advancing sustainable community development in Indonesia: reinforcing local socio-institutional foundations, critically understanding patterns of socio-economic inequality, and systematically integrating collective cultural values such as gotong royong (mutual cooperation). The research is motivated by the recognized limitations of traditional, charity-based philanthropy, which often perpetuates dependency and fails to address the structural roots of poverty. Through a systematic qualitative review and thematic analysis of scholarly literature, the study aims to develop a contextualized transformational philanthropy model. This model is designed to shift the paradigm from passive aid distribution to active community empowerment, positioning local actors as central agents in their own development trajectory. The concluding argument emphasizes that the success of this transformational approach depends on a synergistic balance, merging modern managerial efficiency with deep-rooted local wisdom, aligning religious ethical principles with professional institutional governance, and leveraging digital innovation to foster broad, inclusive participation. Ultimately, the model presents a strategic pathway for philanthropy to contribute meaningfully to long-term, equitable, and resilient community development in the Indonesian context.